Playfulness and digital games in education: Exploring the potential of technology for the teaching and learning process - Filho, Teodoro Antunes Gomes; Correia, Silvia Gomes; Passos, Christian Ricardo Silva; Bomfim , Carlos Eduardo dos Santos; Wagner, Adriano Franzoni; Carvalho , Rejane de; Sena , Jefferson Vitoriano; Silva, Eloísa Helena; Andrade, Sônia Maria de; Rodrigues, Júlia Soares de Campos; Campos, Joana Soares de; Ribeiro, Talyta Maria Aguiar (Seven Editora, 2024)
The objective of this research was to analyze the potential of playful games and digital technologies for the teaching and learning process. To this end, an integrative review research was carried out, which involved the survey of articles on the SciElo and Google Scholar platforms. During the search survey, search descriptors "AND" and "OR" were used in conciliation with specific keywords. In addition, only scientific articles in Portuguese published between 2022 and 2023 were selected. As a result, it was found that the implementation of playful games and technologies in the school environment reveals significant advantages for the teaching-learning process, especially for students with Attention Deficit Hyperactivity Disorder (ADHD). The analysis emphasizes the crucial role of these tools in promoting a dynamic and effective educational approach, although they face challenges such as a lack of technological skills and resources in institutions. The role of the educator in the diversification of teaching strategies is also highlighted, using games as a methodological resource to stimulate learning and increase student participation, resulting in improvements in class performance and dynamics. The continuing education of teachers is highlighted as essential to adopt innovative pedagogical practices, even in the face of obstacles in the implementation of playful activities. It is concluded that the integration of games and technologies in the educational context offers a promising way to improve teaching, highlighting the importance of the role of the educator and the investment in technological resources to provide a more effective and meaningful education. DOI:https://doi.org/10.56238/sevened2024.009-007